STRENGTHENING TEACHER COMPETENCE THROUGH THE DEVELOPMENT OF ISLAMIC EDUCATION MANAGEMENT MODELS BASED ON MORAL AND DIGITAL LITERACY IN THE ERA OF THE INDUSTRIAL REVOLUTION 5.0 AT DAARUL SHAFA ISLAMIC VOCATIONAL HIGH SCHOOL DEPOK - Devi Fatwanti; Fathorrahman; Mamah Siti Rohmah; Irvan Navis; Lismiyani; Lailatul Mutia; Arif Budi Prasetiyo; Sophi Widiya Ningsih; Ilham Amsar Yulistiar (Cakrawala Pedagogik, 2025)
ResearchThis study aims to analyze the strengthening of teacher competence through the development of a model ofmanagement model based on morals and digital literacy in the era of the Industrial Revolution 5.0 at SMK Islam Daarul Shafa Depok.Industrial Revolution 5.0 at SMK Islam Daarul Shafa Depok. By using descriptivequalitative descriptive method through interviews, observations, and documentation, this study found that the management model developed was able to integrate thefound that the management model developed was able to integrate moral values such as trustworthiness, sidqmoral values such as amanah, sidq, tabligh, and fathanah with teachers' digital literacy skills effectively.digital skills of teachers effectively. The results can be seen from the improvement of fourbasic competencies of pedagogical, professional, social, and personality teachers through the utilization of digital technology in learning.utilization of digital technology in learning that remains based on Islamic ethics.Islamic ethics. Learning becomes more interactive, relevant and characterized,while the school management system is more focused in fostering teachers in a sustainable manner.sustainable. This research concludes that strengthening teacher competencethrough the integration of morals and digital literacy is the right strategy,applicable, and needs to be adapted by Islamic education institutions in facing the challenges of the Industrial Revolution 5.0 era.challenges of the Industrial Revolution 5.0 era.Retrieved from.